Bioactive compounds of spontaneous hop and hop in cultivars in the northeast of Portugal - Santos, Briolanja (2022)
Hop, whose scientific name is Humulus lupulus L., is a species of the family Cannabaceae, with climbing, perennial and dioecious characteristics of great importance due to its compounds of interest such as polyphenols and acids. The female inflorescences have glands that secrete mainly lupulin. Hop is known worldwide as an essential raw material and flavoring agent in beer production. Phytochemical compounds from the plant such as xanthohumol, humulone and lupulone have also been used in cosmetics. Moreover, the plant has beneficial properties -anti-inflammatory, antimicrobial, antioxidant. The area of Bragança (Trás-os-Montes) is rich in spontaneous hop and cultivars. The samples of spontaneous hop were collected in different areas of the Bragança district and were analyzed and compared to the varieties of cultivars (Nugget, Polaris, Cascade, Centennial and Chinook). The volatiles extracted from the female cones, in a LikensNickerson system, were analyzed by GC and GC-MS. The α- and β-acids, from where extracted with calibration standard ICE-3 and analyzed by HPLC. Characterization of α- and β-acids, and of the phenolic profile of the Hop samples, was also performed by UHPLC-DAD-ESI-MSn. The cultivars and their respective spontaneous varieties showed similarities in the monoterpenic component, with β-myrcene as the main compound. Regarding HPLC analyses, cultivars showed total values about 15% of α-acids and about 4% of β-acids, while the spontaneous variety showed 7% of α-acids and 9% of β-acids, corresponding to the compounds cohumulona, humulone, colupulona, lupulona and xanthohumol. Quercetin and kaempferol glycosides were also present in some extracts as minor compounds.